(untitled) (World Bulletin of Public Health, 2024)
Among the most important problems of obstetrics and neonatology, one of the first places is occupied by the problem of the immunology of pregnancy and childbirth. Thanks to the introduction of prevention of Rh sensitization by administration of immunoglobulin, its frequency has decreased. At the same time, interest in rare antigens has increased. Intensive continued research in this area emphasizes the importance of prenatal preventive measures to prevent the development of excessive immunization of the fetus and newborn